Flood vulnerability assessment : a multiscale, multitemporal and multidisciplinary approach. Colombian case. (2011)
This article presents a research project in its first phase, whose main objective is to develop a methodology for vulnerability assessment from a multi-scale, multi-temporal and multi-disciplinary perspective, combining the use of indicators and a spatial information system to analyze exposure and vulnerability at regional and local level in specific areas.